(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The efficiency of employing polypyrrole, poly(p-nitroaniline), and p-hydroxyaniline as adsorbents to remove lead (Pb²⁺) ions from aqueous solutions is examined in this work. These functionalized chemicals and conducting polymers have active binding sites and a large surface area, which improves their capacity to absorb heavy metal ions. The study looks at a number of variables that affect adsorption efficacy, such as adsorbent dosage, initial Pb2+ concentration, pH, and contact time. The results reveal that all three materials have a great deal of potential for removing Pb2+ ions, while their efficiency varies according to their surface characteristics and chemical makeup. The results imply that these substances may hold promise for heavy metal-contaminated wastewater treatment applications.